Analisis Sistem Informasi Akuntansi dalam Meningkatkan Efisiensi Pelaporan Keuangan Dinas Sosial Kabupaten Labuhanbatu Utara - Rini Utari; Junita Putri Rajana Harahap (Jurnal Mutiara Ilmu Akuntansi, 2024)
An Accounting Information System (AIS) is a system used to collect, store, process and present accounting information that is relevant and useful for decision making in an organization. The aim of this research is to determine the analysis of accounting information systems in improving the efficiency of financial reporting of the North Labuhanbatu Regency Social Service. This research uses qualitative research methods. The research method used is interviews (in-depth interviews) with research subjects, observation and documentation. The aim of this research is to describe Accounting Information System Analysis in Improving the Efficiency of Financial Reporting for the North Labuhanbatu Regency Social Service. The object of this research is the North Labuhan Batu Social Service. The subjects of this research were North Labuhan Batu social service employees. The data analysis technique used/used in this research is the Descriptive Analysis method. The data collected will be analyzed according to the criteria and things required in data collection. Research also shows that the integration of accounting information systems with other management systems, such as client data management systems and social programs, has improved coordination between departments. Previously, data was often re-inputted and processed separately by each unit, causing data duplication and potential errors. Based on evaluation results, training should be updated periodically to reflect changes in technology and organizational needs. Research shows that a continuous approach to updating training materials and teaching methods can ensure that employees always have relevant and up-to-date information. The North Labuhanbatu District Social Service should consider conducting regular follow-up training to introduce new features of the SIA and address changes in regulations. Based on the results of research related to Accounting Information System Analysis in Improving the Efficiency of Financial Reporting of the North Labuhanbatu Regency Social Service, it can be concluded that this technology significantly increases efficiency, accuracy, transparency and security in financial reporting. The implementation of AIS has reduced manual errors and accelerated the reporting process, enabling more accurate and timely financial reports, as well as supporting better decision making and tighter oversight.